MANAJEMEN KOMUNIKASI TVRI RIAU DALAM MENYAMPAIKAN BERITA TERKINI MELALUI PROGRAM SIARAN DIALOG RIAU CEMERLANG - Apriliani, Nurul Aisyah; Yazid, Tantri Puspita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This brilliant Riau dialogue program is the flagship program of TVRI Riau, because this program presents various fields. For example: education, economy, and many more. This program is also packaged to discuss any issues that are currently being hotly discussed and has sufficient broadcast hours to provide up-to-date information to the people of Riau, especially one of the programs on TVRI Riau which is included in the flagship program for various reasons, especially regarding good broadcast hours so that people can easily and quickly get the information they want This study uses a qualitative method with a descriptive approach. There are ten informants taken through the technique purposife. Types and sources of data were obtained through primary data and secondary data. Data collection was carried out by interviews, observation and documentation. Data analysis techniques by reducing data, presenting data and drawing conclusions. Furthermore, checking the validity of the data was carried out by extending participation and triangulation. The results of this study indicate that the Riau Cemerlang Dialogue Broadcast program on TVRI Riau has succeeded in fulfilling its initial goal of providing useful information and increasing public knowledge about the topics discussed in the program. Through good message delivery strategies, such as using easy-to-understand language, using sophisticated technology and multimedia, and presenting competent speakers in their fields, this program is able to have a positive impact on society. In implementing the Riau Shining Dialog Broadcast program, there is good coordination between the Bidangons involved, so that the program can be implemented properly and on time. Evaluation carried out by the program director for the Riau Brilliant Dialog broadcast program The evaluation carried out by the program director for the Brilliant Riau Dialog Broadcast program on TVRI Riau is very important in ensuring the quality of the program is maintained and continuously improved.